Color detection system using an open path reflection method - Natasha, Baharudin; Hadi, Manap (Universiti Malaysia Pahang, 2018)
Human eye is very capable of differentiating colours; however, people will describe the same tone differently. This weakness makes verbal description inadequate in applications that require precise colour detection and management. Colour measurements are a method of expressing the colours sensed by humans as values. Colour measurements are related to illumination, spectral characteristics of the object, and the spectral sensitivity characteristics of the human eye. As the spectral distribution of the light and the spectral sensitivity characteristics (colour-matching function) of the eye defined in the JIS standards, a colour value can be determined if the spectral reflection of the object is known. On the other hand, the spectral transmittance can be used for the calculation if the light passes through the object. Based on JIS standard, the spectral distribution of the illumination and colour matching function is calculated using multiple conditions. Thus, for each spectral illumination distribution, a different coefficient is set. Consequently, the JIS standard sets different colour matching functions according to the view field. 400 nm to 700 nm in a range of wavelength is required to conduct colour measurements test, which is similar to the wavelength that can be sensed by the human eye. A better solution is to describe colour in numeric terms using adequately calibrated UV spectrometer via open path reflection method. This experiment will be conducted using fibre optic reflection probe. This research will provide some insight into colour perception, measurement and specification, and how the data produced by colour sensors are applied.